Memahami Relasi Komunikasi Orang tua Milenial dalam Pembentukan Konsep Diri Anak di Era Digital - Gusti Restu Kinanti; Wiwid Noor Rakhmad (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2019)
Millennials are a generation that is close to technology. Habits in the use of technology have a profound impact on lifestyle, patterns of thought and values of millennials, even when they become parents. Millennials that have become parents feel for themselves the adverse effects of using these technologies in everyday life. Technology in the millennial era gave rise to addictive traits which made them tend to be apathetic, individual, asocial, preferred something instant and practical, focused on materialistic values, and cared less to help others. Technology has a negative impact on children's development. Meanwhile, children have the nature of imitating their parents in using technology. This study focuses on the relationship of millennial parent communication to children who use technology as a factor in forming the child's self-concept. This study uses a descriptive type of qualitative research. The paradigm used is the interpretive paradigm and uses phenomenological traditions. By using role theory and maintainance relationship theory, this study wants to see the phenomenon of how millennial parents act as role models and maintain communication relationships with children. The results of the study show that millennial parents have awareness about the effects of good and bad for children in using everyday technology. Parents have differences in maintaining relationships between family members by showing behavioral patterns that can affect children's attitudes. In addition, millennial parents know that social interaction is the most important part of a child's personality development, even though parents do not like to socialize with others. Millennials have characters who tend to behave badly due to the frequent use of technology, especially in the scope of information and communication, but millennial parents try so that it doesn't happen to their children. Millennial parents prefer to be a consensual type, namely the type of family that highly values open communication but family authority is a parent.